STABILITAS MIKROEMULSI VCO DALAM AIR PADA VARIASI HLB DARI TIGA SURFAKTAN SELAMA PENYIMPANAN - Indirasvari K. S., Natalie; Permana, I Dewa Gede Mayun; Suter, I Ketut (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 7 No 4 (2018): Jurnal ITEPA, 2018)
Microemulsion is a dispersion system developed from emulsions, which is an oil dispersion system in water, stabilized by a surfactant. Oil-in-water (o/w) microemulsion is an emulsion system suitable for encapsulation and carrier of lipophilic components in the beverage industry. The food grade microemulsion formulation is limited by the type of surfactant that can be used. This research aims to obtain an o/w microemulsion formulation which is stable during storage using three surfactants. In this study, 3 types of food grade surfactants were used, Tween 80, Tween 20, and Span 80, and the oil used is Virgin Coconut Oil (VCO). This research is done in two stages. The first stage of research was the determination of the best microemulsion of 5 variations of HLB: 11, 12, 13, 14, and 15. The second stage is the storage stability test of the microemulsion chosen in the first stage for 7 weeks with observation every week. The data obtained were analyzed by ANOVA. The results of the study shows that HLB 11, 12, 13, 14, and 15 obtained by using 3 surfactants can produce microemulsions. The optimum HLB to obtain the best microemulsion stability is HLB 13. The microemulsion with HLB 13 obtained using 3 surfactants is stable during time of 7 weeks storage.